Reflecting laser-driven shocks in diamond in the megabar pressure range. (8th January 2021) - Jakubowska, K.; Mancelli, D.; Benocci, R.; Trela, J.; Errea, I.; Martynenko, A. S.; Neumayer, P.; Rosmej, O.; Borm, B.; Molineri, A.; Verona, C.; Cannatà, D.; et al.
Abstract: In this work we present experimental results on the behavior of diamond at megabar pressure. The experiment was performed using the PHELIX facility at GSI in Germany to launch a planar shock into solid multi-layered diamond samples. The target design allows shock velocity in diamond and in two metal layers to be measured as well as the free surface velocity after shock breakout. As diagnostics, we used two velocity interferometry systems for any reflector (VISARs). Our measurements show that for the pressures obtained in diamond (between 3 and 9 Mbar), the propagation of the shock induces a reflecting state of the material. Finally, the experimental results are compared with hydrodynamical simulations in which we used different equations of state, showing compatibility with dedicated SESAME tables for diamond.